2021
DOI: 10.2147/bctt.s296242
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Oncoplasty: Breast Conservation in Patients with Large, Multifocal, and Multicentric Breast Cancer

Abstract: Introduction: Extreme Oncoplastic Breast Conservation Surgery (EOBCS) is offered in selected patients with multifocal or multicentric breast cancer (MFMC). Recent evidence has suggested that EOBCS may be a valuable resource for patients with MFMC who may avoid the risk associated with mastectomy in favour of the benefits of breast conservation without risking their oncological outcomes. Our study examined the practice of EOBCS in two regional breast units in Glasgow, United Kingdom. Materials and Methods: A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…In several studies [16, 19], DCIS and ILC were predictive risk factors for positive surgical margins and reoperation. Fischer et al [20] reported that MRI reduced the rate of re-excision for positive margins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several studies [16, 19], DCIS and ILC were predictive risk factors for positive surgical margins and reoperation. Fischer et al [20] reported that MRI reduced the rate of re-excision for positive margins.…”
Section: Discussionmentioning
confidence: 99%
“…These favorable results suggested that eOBCS was an effective treatment option in selected patients. In several studies [16,19], DCIS and ILC were predictive risk factors for positive surgical margins and reoperation. Fischer et al [20] reported that MRI reduced the rate of re-excision for positive margins.…”
Section: Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BCT has limited applications in patients with multifocal or multicentric (MF/MC) disease and in cases of extensive microcalcifications. Though conventionally MF/ MC cancers have been labeled as a contraindication for BCS, with modern extreme oncoplasty, they can be accommodated under the TM fold (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of oncoplastic breast surgery (OBS) was first introduced in the 1990s by Prof. Audretsch when he described the technique of partial reconstruction of the breast using plastic surgical (15)(16)(17). OBS is now increasingly being accepted as the standard of care in the surgical management of breast cancer cases across the world due to benefits such as oncological safety with concurrent improvement in aesthetic results and QoL (5,8,18).…”
Section: Introductionmentioning
confidence: 99%